Discussion - Poterba, James M. (Review of Financial Studies, 1990)
This article examines the linkages between equity markets. The authors present a detailed analysis of the correlations between roughly coincident returns in different equity markets. They also uncover an intriguing fact: The volatility of the London stock market is higher than usual around the time when the NYSE opens. This may support their contagion theory, which argues that traders in one market draw inferences about shocks to share-price fundamentals from observed price movements in other markets. Even price moves which are not generated by fundamentals can therefore affect many markets. The findings raise two basic questions about the comovements in international equity markets. The first is whether there is any reason to expect the correlations across markets to be stable through time. This article emphasizes that returns on the London, New York, and Tokyo markets were more highly correlated around the market break of October 1987 than in other periods....